The importance of the visitation to National Parks and the generation of financial resources - Oliveira Gomes, Paula (2018)
The growing interest in natural areas has also generated greater concern for the preservation of environmental resources. Therefore, this study presents the relation human with the environment and the importance of the generation of financial resources from the visitation in National Parks. Thus, in order to verify the financial importance of the maintenance of protected areas, studies have been applying the environmental valuation methods.